The effect of heat treatment on Fe-Ni/Sic composite - Lai, Moon Yee
The main objectives in this final year project are: to fabricate Fe-Ni/SiC composite via powder metallurgy method, to study on different soaking time of heat treatment for Fe-Ni/SiC composites, and to examine the effect of heat treatment on the Fe-Ni/SiC composites properties.